2022
DOI: 10.1021/acs.jpcb.1c09266
|View full text |Cite
|
Sign up to set email alerts
|

Identifying Single-Stranded DNA by Tuning the Graphene Nanogap Size: An Ionic Current Approach

Abstract: Solid nanopore-based deoxyribonucleic acid (DNA) sequencing has led to low-cost, fast, reliable, controlled, and amplified or label-free and high-resolution recognition and identification of DNA nucleotides. Solid-state materials and biological nanopores have a low signal-to-noise ratio (SNR) and generally are too thick to read at single-nucleotide resolution. The issue with solid-state nanopores is that the DNA strands stick to the nanopore sides and on the surface during the translocation process. The coexis… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
1
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 5 publications
(2 citation statements)
references
References 64 publications
0
1
0
Order By: Relevance
“…Furthermore, toward the development of next-generation DNA sequencing devices which are capable of reading DNA or an entire human genome inexpensively and conclusively leading toward personalized medicine, the role of low-dimensional (2D) materials has emerged into the picture with promising potential, and important research efforts have been dedicated into their development in the past few years. , Interestingly, special attention has been devoted to discovering graphene-based nanodevices, which include graphene nanopores/nanogaps, graphene nanoribbons, ,,, ,,, and carbon nanotubes (CNTs) ,, as potential nanoelectrode materials. Graphene nanopores/nanogaps are outstanding solid-state materials to achieve single-nucleobase resolution due to their one-atom thickness. , Traversi and co-workers have found that the solid-state materials based nanopore combined with the graphene nanoribbon could be used as a nanodevice for the individual identification of DNA nucleobases .…”
Section: Introductionmentioning
confidence: 99%
“…Furthermore, toward the development of next-generation DNA sequencing devices which are capable of reading DNA or an entire human genome inexpensively and conclusively leading toward personalized medicine, the role of low-dimensional (2D) materials has emerged into the picture with promising potential, and important research efforts have been dedicated into their development in the past few years. , Interestingly, special attention has been devoted to discovering graphene-based nanodevices, which include graphene nanopores/nanogaps, graphene nanoribbons, ,,, ,,, and carbon nanotubes (CNTs) ,, as potential nanoelectrode materials. Graphene nanopores/nanogaps are outstanding solid-state materials to achieve single-nucleobase resolution due to their one-atom thickness. , Traversi and co-workers have found that the solid-state materials based nanopore combined with the graphene nanoribbon could be used as a nanodevice for the individual identification of DNA nucleobases .…”
Section: Introductionmentioning
confidence: 99%
“…6 The experimental proof of artificial genetic characters presents a challenge to a low-cost, label-and amplification-free, rapid, and controlled next-generation sequencing (NGS) technique such as nanogap, nanopore, and nanochannel-based smart sensors for healthcare applications. 3,4,[7][8][9][10][11][12][13][14][15][16] In NGS, DNA nucleobases can electrophoretically be passed through nanogaps or nanopores, which changes the ionic or tunneling/ transverse currents, which can be used in real-time sequencing. On the other hand, nanochannel-based devices are also quite promising for NGS applications.…”
Section: Introductionmentioning
confidence: 99%